1980
DOI: 10.1111/j.1365-2125.1980.tb04790.x
|View full text |Cite
|
Sign up to set email alerts
|

Monooxygenase activity of human liver in microsomal fractions of needle biopsy specimens.

Abstract: 1 Methods are described for the determination of mixed function oxidase activity in microsomal fractions from percutaneous needle biopsies of human liver. 2 Activities of needle biopsy samples were comparable with those of wedge biopsy sample obtained at laparotomy from different subjects. 3 Although cytochrome P‐450 content of liver from rat and man was similar, human AHH activity was only 10% of that in the rat. 4 In biopsies with preserved hepatic architecture, AHH activity and cytochrome P‐450 content show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1
1

Year Published

1981
1981
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(26 citation statements)
references
References 32 publications
2
22
1
1
Order By: Relevance
“…Similarly, Boobis et al (1980) have shown that activity of microsomal NADPH cytochrome c-reductase is unaltered by the presence of severe.liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Boobis et al (1980) have shown that activity of microsomal NADPH cytochrome c-reductase is unaltered by the presence of severe.liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue preparation and performance of optical difference spectroscopy were based on methods described in Boobis et al [23], LaBella et al [14] and Whysner and Harding [16].…”
Section: Methodsmentioning
confidence: 99%
“…The K, and Hill values are reported with their corresponding standard errors and standard deviations, respectively. Microsomes from bovine adrenal cortex were prepared in 250 mM KPO4, 150 mM KCI and 1 mM EDTA pH 7.25 and suspended in a 50 mM KPO4, pH 7.25 buffer at 0.5 to 1.0 mg protein ml-' in 1.3 or 3.0 ml quartz cuvettes for spectral determinations (Boobis et al, 1980). Substrates diluted in KPO4 buffer were added in 3 to 5 tl aliquots with equal volumes of buffer added to the reference.…”
Section: Methodsmentioning
confidence: 99%